2019
DOI: 10.1108/ijmpb-04-2018-0064
|View full text |Cite
|
Sign up to set email alerts
|

Do steering committees really steer?

Abstract: Purpose The purpose of this paper is to investigate the confusion among project management practitioners about the role of steering committees. Design/methodology/approach Semi-structured interviews were conducted with highly experienced participants selected from a range of industries and disciplines in Queensland, Australia. Findings Six separate confusions on the role of steering committees were identified within that practitioner community. However, despite participants expressing various opposing view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furthermore, Elonen and Artto (2003) argue that it is often a problem that the roles and responsibilities of the steering committee are unclear. This is discussed further by McGrath and Whitty (2019), who found confusion among practitioners concerning the roles of the steering committee. The findings highlight two important adaptations in the project that addressed this challenge.…”
Section: Steering Committee Features That Build Trustmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, Elonen and Artto (2003) argue that it is often a problem that the roles and responsibilities of the steering committee are unclear. This is discussed further by McGrath and Whitty (2019), who found confusion among practitioners concerning the roles of the steering committee. The findings highlight two important adaptations in the project that addressed this challenge.…”
Section: Steering Committee Features That Build Trustmentioning
confidence: 97%
“…The reason for this may be that steering committees are not very common outside Nordic countries (Andersen, 2008). Another reason may be that there is confusion regarding the role of the steering committees (McGrath and Whitty, 2019). Lechler and Cohen (2009) studied the role of the steering committee in realizing values from project management.…”
Section: Introductionmentioning
confidence: 99%
“…A steering committee is viewed as an instrumental governance mechanism that adds to project governance's sophistication and subsequently forms a key success factor (Meredith & Zwikael, 2020;Drake & Bekker, 2023). Scholars indicate two intertwined motivations for bringing steering committees into existence, which included the introduction of a democratic decisionmaking process to alter the autocratic, hierarchical organisational power structure that exists in large-scale projects and the second to foster collaboration while gaining the benefit of input from multiple sources (stakeholders) in order to enhance projects successes (McGrath & Whitty, 2018;Meredith & Zwikael, 2020;Louw et al, 2021). These are not new, as Karimi et al (2000) had considered the concept of steering committees as a corporate philosophy of having the users take responsibility for planning and controlling the function of specific projects in much the same way that a Board of Directors takes responsibility for planning and controlling the entire company.…”
Section: Literature Review 21mentioning
confidence: 99%
“…Drury (1984) had earlier suggested that 'steering' was a generic term encompassing any committee involved with projects. However, the operation of steering committees since the early 1980s has evidently been problematic, as steering committees needed a standard descriptor for project oversight for failure or success (McGrath et al, 2018). This is even more evident in agricultural projects in which the sector remains least developed in developing nations, while a large-scale project with functional steering committees seems to be the solution to success (IFAD, 2018)…”
Section: Literature Review 21mentioning
confidence: 99%
“…Ninety-seven percent of project managers indicated that they report to a steering group". A further paper surveying practitioners on the subject of steering committees by McGrath and Whitty (2019) has also come to our attention. It identifies six separate confusions concerning steering committees and confirms the model developed by McGrath and Whitty (2013).…”
Section: Literature Reviewmentioning
confidence: 99%